Revisiting the Foundational Assumptions of Fiscal Transparency and Acc ountability Work - Carothers, Thomas; Brechenmacher, Saskia (2018)
The Fiscal Futures team recently updated the foundational assumptions of fiscal transparency and accountability work to fit today’s world. L earn more.